Exploring the Role of Chitosan: A Natural Solution for Plant Disease and Insect Management - Rajkumari Padamini; Pukhram Bhumita; Sanjay Hazarika; Ramesha NM; G R Vishwas Gowda; Kushal Chaturvedi; Chandan Kumar Panigrahi; Rajshree Karanwal (Archives of Current Research International, 2024)
Chitosan is an eco-friendly and multipurpose biopolymer that is obtained from the deacetylation of chitin. It is a polysaccharide with several uses. Chitosan is a useful option in phytopathology because of its biocompatibility, biodegradability, and bioactivity. Two naturally occurring substances that may be used in agriculture to manage plant diseases are chitin and chitosan. It was found that these compounds are toxic and that they prevent the growth and development of fungi. According to reports, they were effective against viruses, bacteria, and other pests. When host plants are exposed to microbial infections, fragments of chitin and chitosan have been shown to elicit activities that trigger a range of defence responses, such as the accumulation of phytoalexins, pathogen-related (PR) proteins and proteinase inhibitors, lignin synthesis, and callose formation. Thus, the goal of this study is to give the reader current knowledge about the use of chitosan formulations as pest and diseases control tools as well as information about their potential uses.